Characterization of the ceramic coating formed on 2024 al alloy by scanning plasma electrolytic oxidation - Xingrui Xu; Weiping Jia; Tingting Yin; Qi Dong; Yutao Ma; Zhen Wang; Zhilong Zhao; Pengxiang Lv (Scientific Reports)
Abstract This study investigates the characteristics and performance of ceramic coatings fabricated on 2024 aluminum alloy surfaces using the scanning plasma electrolytic oxidation (SPEO) process. The effects of various scanning parameters, including discharge gap, scanning frequency, scanning speed, and overlap rate, on coating properties were systematically examined. The coatings were characterized using potentiodynamic polarization, electrochemical impedance spectroscopy (EIS), microhardness testing, roughness analysis, and thickness measurement. The results reveal that optimizing scanning parameters significantly enhances coating performance. The SPEO process enables efficient localized coating deposition through progressive scanning, achieving performance comparable to that of conventional full-surface PEO. Although the high current density associated with the SPEO process generates more surface pores and microcracks, which slightly affect hardness, roughness, and corrosion resistance, the differences are minimal and acceptable for most applications. Furthermore, the SPEO process demonstrates high efficiency in repairing large or complex components, highlighting its significant potential for industrial applications.